FIGURATIVE LANGUAGE IN INDONESIAN KIDS SONGS - Titi Dewi Rohati; Wiruma Titian Adi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The aim of this research is to find out kinds of figurative language in Indonesian kids songs (Burung Kutilang by Ibu Sud, Cicak di Dinding by AT Mahmud, Kasih Ibu by SM Mochtar, Naik Delman by Pak Kasur, Naik Kereta Api by Ibu Sud, Tik Tik Bunyi Hujan by Ibu Sud, Balonku by Pak Kasur, Kembang Apiku by Pak Kasur, Kring Kring Ada Sepeda by Pak Kasur, Si Kancil Nakal by Ibu Sud). Those songs were chosen because easy listening, the words are easy to understand, and those songs are very popular till now eventhough those are old songs. The author got the the song lyrics from website and YouTube. Descriptive qualitative method is used by the author in conducting this research. In this research, the author found five figurative languages in those songs, they are personification, onomatopoeia, simile, metaphore, and symbolism. The most dominant figurative language are personification and onomatopoeia. Those songs have seven personification and seven onomatopoeia. The reason why the song writers use figurative language in their songs because it is easier to remember and can increase children intelligence.